Improved hMSC functions on titanium coatings by type I collagen immobilization. Issue 1 (10th May 2013) - Ao, Haiyong; Xie, Youtao; Tan, Honglue; Wu, Xiaodong; Liu, Guangwang; Qin, An; Zheng, Xuebin; Tang, Tingting
<x xml:space="preserve">Abstract</x> In this study, type I collagen was fixed onto plasma‐sprayed porous titanium coatings by either adsorptive immobilization or covalent immobilization. Surface characterization by scanning electron microscopy (SEM), diffuse reflectance Fourier transform infrared spectroscopy (DR‐FTIR) and X‐ray photoelectron spectroscopy (XPS) confirmed the biochemical modification of the titanium coatings. The immobilizing effects of type I collagen, including variations in the amount and stability of collagen, were investigated using Sirius red staining. A greater amount of collagen was found on the covalently immobilized titanium coating, and higher stability was achieved relative to the absorptive immobilization surface. Human mesenchymal stem cells (hMSCs) were used to evaluate the cytocompatibility of the modified titanium coatings. Type I collagen immobilized on titanium coating led to enhance cell‐material interactions and improved hMSC functions, such as attachment, proliferation, and differentiation. Interestingly, covalently immobilized collagen on titanium coating showed a greater capability to regulate the osteogenic activity of hMSCs than did absorbed collagen, which was explained in terms of the increased amount and higher stability of the covalently linked collagen. The type I collagen covalently immobilized titanium coatings with improved biological function may exhibit better osteointegration in clinical application. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 204–214, 2014.